2011
DOI: 10.1246/cl.2011.1060
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of Tetrasulfur Including Mysterious Rectangular S4 Metal Complexes

Abstract: Of eleven possible isomers for neutral S 4 , rectangular S 4 has been proposed theoretically as one of the most stable forms. There has, however, been no consensus as to the S 4 ground-state geometric structure despite much effort over recent years, because of the lack of direct structural information from experimental work due to lack of preparation in a pure state. The principal question is whether the ground-state geometry is rectangular D 2h or open planar C 2v . Our group found first rectangular S 4 in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…However, if the molecule is floppy, then rigorous calculations of rovibrational states on accurate potential energy surface is needed for prediction of the spectrum and meaningful computation of the partition function. Importantly, electronic structure calculations of potential energy surface for S 4 showed that it is floppy (33,34,38,39). It has a single bond in the middle, consistent with its formation process:…”
Section: Production Of Smentioning
confidence: 69%
“…However, if the molecule is floppy, then rigorous calculations of rovibrational states on accurate potential energy surface is needed for prediction of the spectrum and meaningful computation of the partition function. Importantly, electronic structure calculations of potential energy surface for S 4 showed that it is floppy (33,34,38,39). It has a single bond in the middle, consistent with its formation process:…”
Section: Production Of Smentioning
confidence: 69%
“…Polysulfide anions (S n 2– ) are classic examples of the catenation property of sulfur and are quite well-known in the literature. , The synthesis, structural diversity, and reactivity of an appreciable number of mono-, bi-, and poly nuclear compounds of polysulfide involving transition metals, lanthanides, and main group elements have been reported previously. It may, however, be noted that most of these metal–polysulfido compounds are strictly organometallic compounds. , , ,,,, While reports on several binuclear transition metal-polysulfido compounds are available in the literature, ,,, the majority of these compounds are, however, metal sulfides and clusters with only S-donor ligands (HS – , S 2– , and S n 2– ). Representative examples of such clusters include [Cu 2 (S 3 )­(S 4 )] 2– , [Ni 2 (μ-S 4 )] 2+ , [Ni 2 (μ-S 5 )] 2+ , [Co 2 (μ-S 4 )] 2+ , [Co 2 (μ-S 5 )] 2+ , [Fe 2 (μ-S 5 )] 2+ , [Fe 2 (μ-S 4 )] 2+ , [Fe 2 (μ-S) 2 (S 5 ) 2 ] 2– , [S 5 Fe­(μ-S) 2 FeS 5 ] 2– , [Mn 2 (μ-S 4 )] 2+ , and [Mn 2 (μ-S 5 )] 2+ as well as few higher nuclearity clusters .…”
Section: Introductionmentioning
confidence: 97%